2012
DOI: 10.1007/s11010-012-1241-y
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 is implicated in early steps of the differentiation of pre-adipocytes into adipocytes

Abstract: Protein kinase CK2 is a ubiquitously expressed serine/threonine kinase which is composed of two catalytic α- or α'-subunits and two non-catalytic β-subunits. CK2 has been shown to be implicated in embryogenesis, spermatogenesis, and the development of certain organs but its role in basal differentiation processes is only sparsely analyzed. 3T3-L1 cells, which are murine pre-adipocytes, can be induced to differentiate into mature adipocytes within 2 weeks using a combination of insulin, dexamethasone, and isobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…In another study, which analysed the differentiation of preadipocytes into adipocyctes it was shown that the CK2 kinase activity increased at the beginning of the differentiation process and decreased with ongoing differentiation. Moreover, inhibition of the CK2 kinase activity at the beginning of the differentiation for up to 6 days after start of differentiation prevents differentiation whereas after day 6 there was no inhibition of differentiation anymore [43]. Thus, these results are in a good agreement with the data presented here for neural differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…In another study, which analysed the differentiation of preadipocytes into adipocyctes it was shown that the CK2 kinase activity increased at the beginning of the differentiation process and decreased with ongoing differentiation. Moreover, inhibition of the CK2 kinase activity at the beginning of the differentiation for up to 6 days after start of differentiation prevents differentiation whereas after day 6 there was no inhibition of differentiation anymore [43]. Thus, these results are in a good agreement with the data presented here for neural differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…The consensus sequence contains serine or threonine residues surrounded by acidic amino acids [17]. This kinase is involved in various cellular processes, including proliferation, differentiation, apoptosis and angiogenesis [18][19][20][21]. However, the specific function of CK2 on leukocyte-endothelial cell interaction during TNF-α-induced inflammation remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown by several groups that CK2 seems to be an important protein kinase for a variety of different cellular processes in developing organs and organogenesis [5,6,26,27]. In the differentiation of pre-adipocytes into adipocytes, CK2 was found to be accompanied by a decrease in the protein level and in the kinase activity [28,29]. Inhibition of CK2 kinase activity at the beginning of the differentiation process prevented differentiation, whereas, inhibition of CK2 activity at later time points had no effect on the differentiation process, which indicates that CK2 only plays an early role in differentiation of pre-adipocytes into adipocytes [28].…”
mentioning
confidence: 99%
“…In the differentiation of pre-adipocytes into adipocytes, CK2 was found to be accompanied by a decrease in the protein level and in the kinase activity [28,29]. Inhibition of CK2 kinase activity at the beginning of the differentiation process prevented differentiation, whereas, inhibition of CK2 activity at later time points had no effect on the differentiation process, which indicates that CK2 only plays an early role in differentiation of pre-adipocytes into adipocytes [28]. There is another example where CK2 contributes to differentiation processes of cells.…”
mentioning
confidence: 99%